2023
DOI: 10.1038/s41598-023-43660-3
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of PLA by exploring the power of MWCNTs in enhancing thermal, mechanical properties, and weathering resistance

Mohammed M. Younus,
Hamdy M. Naguib,
Mohamed Fekry
et al.

Abstract: The present study focuses on enhancing the mechanical, thermal, and degradation behavior of polylactic acid (PLA) by adding carbon nanotubes (CNTs) with different concentrations of 0.5, 1, 3, and 5%. The CNTs were prepared using catalytic chemical vapor deposition, and the prepared PLA/CNTs nanocomposite films were characterized using techniques such as FT-IR, Raman spectroscopy, TGA, SEM, and XRD. The distinct diffraction patterns of multi-walled carbon nanotubes (MWCNTs) at 2θ angles of 25.7° and 42.7° were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…23,37,38 D and G bands, centered at 1360 and 1580 cm −1 in spectra, were associated with the vibration of carbon atoms in a disordered graphite structure and an ordered graphic structure, respectively. 39,40 Lower ratios of I D /I G of TLCP-N5 (1.12) than TLCP-N0 (1.44) indicated that TLCP-N5 possessed a higher graphitization degree and a more compact char layer. 41−43 Thus, the condensation phase played a dominant role in the flameretardant mechanism of TLCP-N5.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23,37,38 D and G bands, centered at 1360 and 1580 cm −1 in spectra, were associated with the vibration of carbon atoms in a disordered graphite structure and an ordered graphic structure, respectively. 39,40 Lower ratios of I D /I G of TLCP-N5 (1.12) than TLCP-N0 (1.44) indicated that TLCP-N5 possessed a higher graphitization degree and a more compact char layer. 41−43 Thus, the condensation phase played a dominant role in the flameretardant mechanism of TLCP-N5.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…It suggested that the combination of the polymer bulk and the nanofibrous structure in TLCP-N5 was conducive to the formation of a high-quality char layer, thus inhibiting the diffusion of oxygen and suppressing heat transfer during combustion . The degree of graphitization of TLCP residues was represented by the ratio of the integrated intensities of the D and G bonds (Figure F). ,, D and G bands, centered at 1360 and 1580 cm –1 in spectra, were associated with the vibration of carbon atoms in a disordered graphite structure and an ordered graphic structure, respectively. , Lower ratios of I D / I G of TLCP-N5 (1.12) than TLCP-N0 (1.44) indicated that TLCP-N5 possessed a higher graphitization degree and a more compact char layer. Thus, the condensation phase played a dominant role in the flame-retardant mechanism of TLCP-N5. The formation of a dense char layer during burning could inhibit the combustible gaseous release and heat exchange, which is shown in Figure G.…”
Section: Resultsmentioning
confidence: 99%
“…These included a band around 3400 cm −1 , representing the stretching vibration of hydroxyl groups (OH), and a band at 1750 cm −1 , signifying the stretching vibration of the carbonyl group (CO) within the ester linkage of PLA. Additionally, there are bands around 2997 cm −1 , which are associated with the stretching vibration of CH bonds in the methylene (CH 3 ) groups of PLA, and bands around 1180 cm −1 , corresponding to the stretching vibration of CO bonds [ 24 , 25 , 26 , 27 ]. After 30, 180, and 300 days of fiber exposure to field conditions, minimal changes were observed in these characteristic bands, which were suggestive of minor alterations in the chemical structure but not proof of mulch degradation.…”
Section: Resultsmentioning
confidence: 99%
“…PLA shows a storage modulus of about 3400 MPa, which corroborates findings reported in previous studies on PLA. 47,48 This plot offers insights into the viscoelastic behavior of PLA, revealing three distinct domains: rigid (glassy state), α-relaxation related to the glass transition, and rubbery state. In the glassy state, the macromolecular chains are tightly packed and the subglass β relaxation attributed to the rotational movement of ester groups within PLA appears slightly.…”
Section: Resultsmentioning
confidence: 99%